HSPA1A inhibits pyroptosis and neuroinflammation after spinal cord injury via DUSP1 inhibition of the MAPK signaling pathway - Xuegang He; Bo Deng; Cangyu Zhang; Guangzhi Zhang; Fengguang Yang; Daxue Zhu; Yong Yang; Bing Ma; Xuchang Hu; Yonggang Wang; Xuewen Kang (Molecular Medicine)
Abstract Background Inflammation and proinflammatory programmed cell death, referred to as pyroptosis, are important causes of poor functional recovery after traumatic spinal cord injury (TSCI). Heat shock protein family A member 1A (HSPA1A) is a molecular chaperone protein that is highly expressed after TSCI and is thought to be neuroprotective. However, the mechanisms underlying the protective effects of HSPA1A after TSCI are unclear. Methods The levels of pyroptosis and inflammation after TSCI were determined by enzyme-linked immunosorbent assay (ELISA) and western blotting analysis. The role of HSPA1A in regulating pyroptosis and inflammation in TSCI was verified by in vivo and in vitro experiments. The molecular mechanism of the effects of HSPA1A in TSCI was elucidated by bioinformatics and coimmunoprecipitation analyses. Results Pyroptosis and inflammation are significantly increased after TSCI. HSPA1A overexpression in microglia attenuated nigericin- and lipopolysaccharide (LPS)-induced pyroptosis and inflammation in vitro, whereas knockdown of HSPA1A aggravated pyroptosis and inflammation. In vivo, overexpression of HSPA1A reduced tissue damage, nerve cell death, pyroptosis, and inflammation in TSCI rats and promoted functional recovery. Mechanistically, we identified that HSPA1A interacts with dual specificity phosphatase 1 (DUSP1) and inhibits activation of the mitogen-activated protein kinase (MAPK) pathway, thereby attenuating pyroptosis and inflammation. Conclusion HSPA1A reduces pyroptosis and inflammation after TSCI by upregulating DUSP1 and inhibiting MAPK pathway activation. HSPA1A activation has potential as a therapeutic approach to promote functional recovery after TSCI.